Teachers’ Beliefs about Differentiated Instructions in Mixed Ability Classrooms: A Case of Time Limitation - Jaweria Aftab (Journal of Education and Educational Development, 2020)
Students in today’s mixed ability classrooms come from diverse backgrounds with needs. In such a scenario, differentiated instructions are of prime importance for teachers to deal with in mixed ability classrooms. The teaching experiences and academic life mould perceptions of teachers which effects their teaching style; therefore, it is important to know teachers’ beliefs and perceptions regarding teaching in a mixed ability classroom at middle school level so as to guide educators and heads inside and outside the institution. For this study, quantitative research method was used to explore and understand the beliefs and perceptions of the teachers of middle schools regarding implementing differentiated instructions. The sample size included 120 teachers who were sent a survey questionnaire through online Google form and was constructed by customizing the questionnaire from Ballone and Czerniak (2001). The analysis of quantitative inquiry revealed that there is a positive association between teachers’ beliefs about their intentions and stakeholders’ expectations to implement differentiated instruction. It was highlighted that all stakeholders wanted teachers to implement differentiated strategies; however, the teachers were found to be short of planning and instructional time for differentiation.
Keywords: differentiated instructions; mixed ability classrooms; teachers’ beliefs; multiple intelligence